July 26 : day of world solidarity with the Cuban revolution - Martinez (OSPAAAL (Organization of Solidarity with the People of Asia, Africa and Latin America), 1965)
A chain being burst with a large red shape with indigenous design bursting from between the links Poster in four languages advertising the day of solidary with the Cuban revolution, 26 July PO-1358